What Works in Conservation 2017 - Nancy Ockendon
This book provides an assessment of the effectiveness of 763 conservation interventions based on summarized scientific evidence. Chapters cover the practical global conservation of amphibians, bat and birds, conservation of European farmland biodiversity and some aspects of enhancing natural pest control and enhancing soil fertility. The 2017 edition contains a new chapter covering conservation of forests, and an extended chapter on control of freshwater invasive species. It contains key results from the summarized evidence for each conservation intervention and an assessment of the effectiveness of each by international expert panels. The accompanying website www.conservationevidence.com describes each of the studies individually, and provides full references.